Traumatic Burst Fracture with Spinal Channel Involvement Augmentation with Bioactive Strontium-Hydroxyapatite Cement - S. Masala; E. Calabria; G. Nano; R. Iundusi; L. Greco; R. Di Trapano; U. Tarantino; G. Simonetti (Case Reports in Orthopedics)
In November 2011 a 75-year-old man was admitted to our emergency department with a low back pain caused by a traumatic L1 vertebral collapse with backward projection of posterior wall superior third. The indication for neurosurgical instrumentation was placed, although he refused the treatment. Hence he was treated conservatively without a significant improvement up to January 2012 when, still refusing surgery, he accepted to undergo percutaneous vertebroplasty with a novel bioactive injectable strontium-hydroxyapatite cement. Vertebroplasty was performed without complications. A CT scan, performed the day after the procedure, ruled out extravertebral cement leakage. Pain improvement was significant (preprocedure VAS 10, one-week VAS 4) with a gradual decrease up to three months when it stabilized at 2. CT examination after 1 year showed a good cement osseointegration with osteophytic spurs bridging the superior endplate of the level involved to the inferior one of the level above. The new bone ingrowing property of the strontium-hydroxyapatite containing cement permits to extend the treatment indication also to unstable collapses in which the risk of pseudoarthrosis is very high. In this reported case we evaluated the potential role of percutaneous vertebroplasty in traumatic burst fracture with spinal channel involvement.